2010
DOI: 10.1024/1422-4917.a000016
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy-, Temperaments- und Charakterdimensionen bei inhaftierten Mädchen

Abstract: The results confirm the existence of the psychopathy construct in female delinquents, though the percentage of girls with core psychopathy dimensions is very small. The differentiating temperament factors found among girls scoring high on psychopathy dimensions as opposed to girls without psychopathy indicate that psychopathy is a valid construct that can identify a specific subgroup of antisocial girls with core psychopathy symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…an intrinsically lower sensitivity to social rewards, such as praise (Cloninger et al , 1994; Lahey et al , 2003). Several studies in juvenile offenders (Atarhouch et al , 2004) and incarcerated girls (Sevecke et al , 2010) with CD confirmed this relationship. Evidence from twin and adoption studies has indicated that CD (without CU) is moderately heritable, with about half of the variance being explained by genetic make-up (for review see Glenn et al , 2013) and a substantial environmental contribution (Viding and McCrory, 2012).…”
Section: Introductionmentioning
confidence: 75%
“…an intrinsically lower sensitivity to social rewards, such as praise (Cloninger et al , 1994; Lahey et al , 2003). Several studies in juvenile offenders (Atarhouch et al , 2004) and incarcerated girls (Sevecke et al , 2010) with CD confirmed this relationship. Evidence from twin and adoption studies has indicated that CD (without CU) is moderately heritable, with about half of the variance being explained by genetic make-up (for review see Glenn et al , 2013) and a substantial environmental contribution (Viding and McCrory, 2012).…”
Section: Introductionmentioning
confidence: 75%
“…The JTCI was used in various representative clinical samples [ 64 , 66 ]. It shows a good reliability and validity [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Second, as there are indications for specific differences between boys and girls regarding either psychopathic or CU traits (e.g. [103, 222224], gender issues seem to need more attention as well. Third, as Hong Kong children were found to have higher scores on CU traits than United States children [45], cultural issues might play an important role as well.…”
Section: Future Researchmentioning
confidence: 99%